Influência da época de semeadura em caracteres agronômicos, adaptabilidade e estabilidade de cultivares de soja - Bicalho, Thaís Ferreira (2018)
The identification of cultivars that combine high productive potential, wide adaptation and stability for different environments is of notable interest to breeders and producers. The existence of the genotypes by environments interaction (GxA) hinders the process of selection and recommendation of cultivars. The objective of this research was to evaluate the effect of sowing times on the agronomic traits, adaptability and phenotypic stability for the grain yield character of fifteen soybean cultivars, in the city of Uberlândia - MG. The trials were conducted at Fazenda Capim Branco (latitude 18º53'19 ''S, longitude 48º20'57''W), in a randomized complete block design with three replications. Ten agronomic characters were evaluated, being: number of days for flowering and maturity, height of plants at flowering and maturity, number of nodes at main stem at flowering and at maturity, height of first pod insertion, total number of pods per plant, number of seeds per pod and grain yield, besides adaptability and stability, in fifteen soybean cultivars. The evaluations of the agronomic characters were carried out in the useful plot, which was formed by two plant center lines, 4 m long and spaced 0.5 m between rows. The data obtained was submitted to individual and joint analyzes, and when differences between the treatments were observed for the characteristics evaluated by the F test, the means were grouped by the Scott-Knott test. The cultivar interaction was verified by sowing times, the decomposition in simple and complex parts was carried out, proposed by the method of Cruz and Castoldi (1991). In this study, predominantly, there was interaction of the complex type, and there was then differential phenotypic expression of the cultivars before the four sowing seasons. The behavior was detailed by the methods of adaptability and stability proposed by Eberhart and Russel (1966), Lin and Binns (1988), modified by Carneiro (1998), AMMI and Centroide. For the productive performance study, the cultivars that stood out were: TMG 7062 IPRO, NS 6909 IPRO, CD 2737 RR, TMG 2158 IPRO and UFUS 7415, in the four sowing seasons. Regarding the adaptability and productive stability, the cultivar CD 2737 RR presented high grain yield, wide adaptation and predictability of behavior, in the four sowing times, in the evaluated methods. Considering the methods of Eberhart and Russel (1966) and Lin and Binns (1988), modified by Carneiro (1998), the cultivar NS 6909 RR was classified for favorable environments, whereas, by Lin and Binns (1988), modified by Carneiro 1998), and Centroide, the cultivar that emerged under these cultivation conditions was UFUS 8301. For the AMMI method, UFUS 7415, CD 2737 RR and UFUS Millionaria are considered to be stable and widely adapted.